Miestų žaliosios erdvės socialinių ir ekonominių interesų balanso aspektu - Stauskas, Vladas (Journal of Architecture and Urbanism, 2006)
Urban green spaces in view of balance between social and economic interestsWhen discussing the priorities and leverage in urban development, we usually use such concepts as „economic potential“, „financial investment“, „a great quantity of constructions1“, etc. However, the final result should in fact strive for human happiness, health, love for your city, wish to live there.The urban structure of a city always contains a system of open green spaces. These areas are important not only from ecological and aesthetical point of view, but also for social communication as well as raising the economic value of plots. The paper, giving an example of contemporary development of the resort of Palanga, deals with tendencies and problems resulting from the privatization process and great mistakes in locating urbanized plots in the areas of the Lithuanian seaside. The areas, which in the Master Plan are foreseen for new parks, forests and hydroparks, started to be used for construction of private buildings.Generally, in Lithuania not only resort areas, but also any open spaces and even outer wood areas suffer from a bad tendency to treat them exceptionally as potential plots for building construction. In the case of Palanga we meet with the danger of continuous urbanization of the seaside, what consequently means decrease of the quality of the resort as well as fall in land prices in future.Progressive examples from foreign countries and the European Union directives are given, where the quantity of green areas in a city is considered as one of the most important criteria of its modernity and quality.The paper is based on a continuous experience of the author and on the recent work at Institute of Architecture and Contraction on the impact of land privatization on land prices and urban development. Reasonable balance between private and public interests is nesessary, and we still lack it.Article in Lithuanian.Santrauka. Analizuojami viešųjų ir ypač žaliųjų erdvių ir visuomenei neprieinamų privačių teritorijų santykio su grynai ekonominiais interesais klausimai. Pateikiama naujausia Palangos pajūrio zonos tyrimo medžiaga, taip pat pavyzdžių iš kitų miestų ir kurortų. Palangos situacija palyginama su kitų šalių pavyzdžiais.Reikšminiai žodžiai: žaliosios erdvės, visuomenė, privatumas, interesai, ekonomika, teritorija, pusiausvyra.First Published Online: 21 May 2013